2020
DOI: 10.15561/20755279.2020.0408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of three sport games in physical education on the health-related fitness of male university students

Abstract: Background and Study Aim. Few controlled studies have been conducted on the effect of sports games as a physical education (PE) course on the health-related fitness of university students. The aim of the study was to determine whether three sports in a PE course will help improve the health-related fitness of male university students. Material and Methods. Students from two universities participated in the study, with one university acting as a control group. There were two PE courses which students regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…2013 , Lee et al . 2021 , Mohammed 2020 ). The agility of the participants was evaluated using the Modified T test which is a reliable test for clinical assessment ( Sassi et al .…”
Section: Resultsmentioning
confidence: 99%
“…2013 , Lee et al . 2021 , Mohammed 2020 ). The agility of the participants was evaluated using the Modified T test which is a reliable test for clinical assessment ( Sassi et al .…”
Section: Resultsmentioning
confidence: 99%
“…The group that did conventional exercises or the group that was not given treatment (group C) could increase speed, agility, and leg muscle power in badminton players because badminton is a sport that has benefits in increasing physical fitness in adolescents, including: increasing muscle endurance, strength, power, flexibility, and cardiorespiratory fitness (Fernandez-Fernandez et al, 2013;Lee et al, 2021;Mohammed, 2020;Stovba et al, 2019). One's involvement in badminton can improve all aspects of physical health, particularly heart and lung function and basic physical capacities (Cabello-Manrique et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the benefits of badminton in terms of improving physical fitness, five studies reported benefits in adolescents of both sexes, such as improved muscular strength and endurance, explosive strength, power, flexibility, and cardiorespiratory fitness [ 26 , 34 , 35 , 73 ], obtaining significant improvements in all of the aforementioned parameters, with the only exception being body composition [ 35 ].…”
Section: Discussionmentioning
confidence: 99%